Mental fatigue and sleep restriction effects on perceptual-cognitive performance in trained beach volleyball athletes - Barbosa, Bruno Teixeira; de Lima-Junior, Dalton; Moreira, Alexandre; Nakamura, Fábio Yuzo; Batista, Gilmário Ricarte; Faro, Heloiana; Fortes, Leonardo de Sousa (Frontiers in Psychology, 2025)
IntroductionPerceptual-cognitive skills are essential in sports such as beach volleyball. Mental fatigue (MF) and sleep restriction (SR) are known to impair athletes’ perceptual-cognitive performance. This study aimed to analyze the effects of MF and SR on perceptual-cognitive performance in beach volleyball athletes.MethodsFourteen volunteers participated (12 men; 17.9 ± 1.2 years; 182.0 ± 7.7 cm; 72.3 ± 8.4 kg) and were randomly submitted to four experimental conditions: (a) Control (CT), (b) MF, (c) SR, and (d) SR + MF. The MF cognitive load and SR duration were individualized in MF and SR experimental conditions. Perceptual-cognitive performance was assessed through two visuomotor tests utilizing LED light technology to simulate defensive and blocking actions within a real beach volleyball context. Visuomotor tests assessed reaction time (RT) measures. The Generalized Linear Models were applied to verify the main effects of the conditions for the perceptual-cognitive responses.ResultsThe results showed a significant condition effect for both the defense [X2(3,39) = 212.2; p < 0.001] and block tests [X2(3,39) = 104.0; p < 0.001]. In the defense test, participants in the CT condition had significantly faster RTs (1727.0 ± 113.0 ms; p < 0.001) compared to all other conditions (MF: 1806.0 ± 126.0 ms; SR: 1874.0 ± 145.0 ms; and SR + MF: 1906.0 ± 133.0 ms). Additionally, the SR and SR + MF conditions showed slower RTs than MF (p = 0.004 and p < 0.001, respectively), with no significant difference between SR and SR + MF (p = 0.41). In the block test, the CT condition also resulted in faster RTs (631.0 ± 82.2 ms; p < 0.001) compared to MF (711.0 ± 77.5 ms), SR (691.0 ± 82.3 ms), and SR + MF (722.0 ± 100.0 ms). SR had better RTs than MF (p = 0.04) and SR + MF (p = 0.01), with no differences between MF and SR + MF (p = 0.61).ConclusionTherefore, we conclude that both the isolated and combined effects of MF and SR negatively impact RT in the defense and block visuomotor tests. This suggests that MF and SR conditions may impair athletes’ ability to respond quickly to visual stimuli in different scenarios.